PENGEMBANGAN KURIKULUM BEST PRACTISE JUARA (JUMAT HAFALAN SURAH JUZ 30) DI SD NEGERI NGEMPLAK 1, SLEMAN: Indonesia - Yustina Herawati; Dhiniaty Gularso (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze curriculum development through the Best Practice JUARA (Jumat Hafalan Surah Juz 30) program at SD Negeri Ngemplak 1 Sleman. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the principal, teachers, students, and parents. Data validity was ensured through source and technique triangulation, while data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings revealed that the JUARA program was developed through systematic planning, implementation, and evaluation stages. The program is conducted every Friday using talaqqi, tasmi’, and muraja’ah methods through the Ummi approach. The program has improved students’ memorization of Juz 30, tajwid accuracy, and fluency in Qur’anic recitation. In addition, it has contributed positively to the development of students’ religious character, discipline, responsibility, perseverance, and self-confidence. The JUARA program demonstrates a successful practice of religious-based curriculum development in elementary schools.